Relationship between a Doctor and a Patient with Mental Disorder - Plesničar, Blanka Kores (Medicine, Law & Society, 2016)
Quality relationship between a doctor and a patient with mental disorder is pivotal to successful treatment. The doctor, the patient and the environment contribute numerous factors to this relationship. There are also ethical and legal aspects to consider, and above all, it is intrinsically linked with the patient's trust. However, the relationship between a doctor and a patient with mental disorder may lead to crossing professional boundaries and even to their violation. Crossing boundaries means deviating from normal standards of practice that does not exploit or harm the patient, and can be even beneficial to the later; violation of boundaries is harmful to the patient and serves primarily for satisfying the needs of the doctor. Education and learning ethical norms and communication techniques represent the foundation of all professional relationships.